Pengamalan Nilai Nilai Pancasila Dalam Kehidupan Berbangsa Dan Bernegara Dengan Menumbuhkan Rasa Kesadaran Melalui Hak Dan Kewajiban - Ari Metalin Ika Puspita; Kenyo Wangsa Euanggelion; Satria Al Fauzi Ramadhan; Bintang Purnama Putra (Pusat Riset dan Inovasi Nasional, 2024)
This article analyzes and explains the implementation of Pancasila values in national and state life by fostering a sense of awareness through rights and obligations. Pancasila is not only the basis of the state but also a guideline for Indonesian citizens, because Pancasila is the identity of the nation and with its rights and obligations, people have a sense of belonging as citizens. There are several efforts that can be made to practice Pancasila and increase public awareness, namely 1) Education, 2) Starting from oneself, 3) Starting from small things, and the rest is the hope that society will truly have national and state awareness.